FYR Macedonia : Report on the Observance of Standards and Codes on Accounting and Auditing, Update - World Bank (2015)
This assessment of accounting and auditing requirements and practices in Former Yugoslav Republic (FYR) Macedonia is part of a joint initiative implemented by the World Bank and the International Monetary Fund to prepare reports on the observance of standards and codes (ROSC). The assessment focuses on the strengths and weaknesses of the accounting and auditing (A and A) environment that influences the quality of corporate financial reporting, and includes a review of both statutory requirements and actual practice. The assessment also considers the extent of compliance with European Union (EU) requirements under the acquis communautaire. The strategic objective of this report is to support government efforts to improve the business climate in FYR Macedonia, and achieve the country s overarching goal of EU integration. The three essential pillars of institutional infrastructure are: (i) adequate and appropriate legal requirements, (ii) capacity sufficient to implement those requirements, and (iii) effective enforcement mechanisms. This report updates the first ROSC A and A prepared in 2003. This report provides policy recommendations to improve financial transparency in the domestic corporate sector and to strengthen accounting and audit practices in line with international benchmarks and EU Directives.